Lost and Found: Piwi and Argonaute Pathways in Flatworms - Fontenla, Santiago; Rinaldi, Gabriel; Tort, Jose F. (Frontiers in Cellular and Infection Microbiology, 2021)
Platyhelminthes comprise one of the major phyla of invertebrate animals, inhabiting a wide range of ecosystems, and one of the most successful in adapting to parasitic life. Small non-coding RNAs have been implicated in regulating complex developmental transitions in model parasitic species. Notably, it has been postulated that parasitic flatworms have lost Piwi RNA pathways but gained a novel Argonaute gene. Herein, we analyzed, contrasted and compared the conservation of small RNA pathways among several free-living species (a paraphyletic group traditionally known as ‘turbellarians’) and parasitic species (organized in the monophyletic clade Neodermata) to disentangle possible adaptations during the transition to parasitism. Our findings showed that complete miRNA and RNAi pathways are present in all analyzed free-living flatworms. Remarkably, whilst all ‘turbellarians’ have Piwi proteins, these were lost in parasitic Neodermantans. Moreover, two clusters of Piwi class Argonaute genes are present in all ‘turbellarians’. Interestingly, we identified a divergent Piwi class Argonaute in free living flatworms exclusively, which we named ‘Fliwi’. In addition, other key proteins of the Piwi pathways were conserved in ‘turbellarians’, while none of them were detected in Neodermatans. Besides Piwi and the canonical Argonaute proteins, a flatworm-specific class of Argonautes (FL-Ago) was identified in the analyzed species confirming its ancestrallity to all Platyhelminthes. Notably, this clade was expanded in parasitic Neodermatans, but not in free-living species. These phyla-specific Argonautes showed lower sequence conservation compared to other Argonaute proteins, suggesting that they might have been subjected to high evolutionary rates. However, key residues involved in the interaction with the small RNA and mRNA cleavage in the canonical Argonautes were more conserved in the FL-Agos than in the Piwi Argonautes. Whether this is related to specialized functions and adaptations to parasitism in Neodermatans remains unclear. In conclusion, differences detected in gene conservation, sequence and structure of the Argonaute family suggest tentative biological and evolutionary diversifications that are unique to the Platyhelminthes. The remarkable divergencies in the small RNA pathways between free-living and parasitic flatworms indicate that they may have been involved in the adaptation to parasitism of Neodermatans.